Select issues in pain management for the youth and adolescent athlete (Medicine & Science in Sports & Exercise, 2020)
This document provides an updated overview of select pain management issues that are important to team physicians who are responsible for the medical care of youth and adolescent athletes. It is not intended as a standard of care and should not be interpreted as such. This document is only a guide and, as such, is of a general nature, consistent with the reasonable, objective practice of the health care professional. Individual treatment will turn on the specific facts and circumstances presented to the physician. Adequate insurance should be in place to help protect the physician, the athlete, and the sponsoring organization.